Ceramic provenance and the regional organization of pottery production during the later Formative periods in the Valley of Oaxaca, Mexico: Results of trace-element and mineralogical analyses. (August 2016) - Minc, Leah D.; Sherman, R. Jason; Elson, Christina; Winter, Marcus; Redmond, Elsa M.; Spencer, Charles S.
Abstract: The Valley of Oaxaca, Mexico represents an extremely complex geological context for ceramic provenance studies. Here we utilize this complexity to establish a fine-grained ceramic geography for the central portion of the valley, by combining extensive raw material survey with chemical and mineralogical characterization of clays and pottery. Trace element analyses of 320 field clays and 500 vessels distinguish twelve different areas that were actively producing ceramics during later Middle through Terminal Formative times (700 BCE–200 CE). These detailed provenance determinations provide a means to track changes in the organization of ceramic production at the core of the emerging Zapotec state, and contribute fresh insights to long-standing economic questions - such as the rise of early market systems - in the Valley of Oaxaca. Highlights: Field clays in the Valley of Oaxaca, Mexico have been sampled in over 300 locations and characterized via INAA and petrography. A regional reference map of clay composition has been developed for use in ceramic provenance determination. Based on a sample of 500 ceramics, at least 12 different areas were producing Formative pottery. Provenance data are used to examine the scale and organization of exchange relative to the rise of the Zapotec state.